Corona virus-19 preventive practices among primary health workers in Owo local government, Ondo state Nigeria - Kareem, Abiodun J.; Kareem, Adesola O.; Ogunromo, Ayodele Y.; Ahmed, Liasu A.; Babalola, Babatunde D. (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) is an infectious disease with high mortality. Healthcare workers are at the frontline of COVID-19 response and are prone to infection. Therefore, healthcare workers’ preventive practices cannot be underestimated. The study aimed to determine the COVID-19 preventive practices among primary health workers in Owo, Local Government, Ondo state Nigeria. Methods: This was a descriptive cross-sectional study. Consenting staff of primary health centres completed a pretested self-administered questionnaire. The data were analysed using descriptive and inferential statistics. Results: A total of 400 respondents were recruited with 91 (22.8%) males and 309 (77.2%) females giving male to female ratio of 1:3.4. The age range of the respondents was 19-61 years with a mean age of 37.1 (8.1) years. More than half (58.0%) had tertiary level of education and most participant were community health extension workers (36.7%). Majority (99.8%) of the workers were aware of COVID-19 though 212 (53.0%) had good knowledge. The major source of information was the television (94.3%). About 351 (87.8%) had positive attitude despite 383 (95.7%) agreeing that COVID-19 is a problem in Nigeria. More than three-quarter (76.5%) had good practice. There was a significant relationship between knowledge (χ2=29.072, p<0.001), attitude (χ2=35.156, p<0.001) with practice. Educational level was the only factor associated with adherence to COVID-19 guideline (χ2=5.256; p=0.022). The predictors of good practice include knowledge (95% CI =2.296-6.269; p<0.001) and attitude (95% CI =3.079-10.767; p<0.001). Conclusions: The health workers had good knowledge, positive attitude and good preventive practices towards COVID-19.